'Antecedents' and 'postcedents' in relation to satisfaction in Taiwanese business relationships. (4th January 2010) - Lee, Tzong-Ru (Jiun-Shen); Svensson, Goran; Mysen, Tore
The research objective is to test whether satisfaction in business relationships may constitute a mediating construct between trust and commitment on the one hand, and coordination, cooperation and continuity expectancy on the other. The structural relationships are summarised in an AMP-model (i.e., antecedents, mediator and postcedents), the sample at that time consisted of attitudes among leading executives in small and medium-sized companies in Taiwan. The tested structural relationships of the AMP-model complement previous theory and research of antecedents and postcedents in relation to satisfaction in business relationships. One contribution is that the empirical findings indicate that satisfaction in studied buyer-supplier relationships may be seen as a mediating construct between antecedents (such as trust and commitment) and postcedents (such as coordination, cooperation and continuity). Research limitations and suggestions for further research are provided.